Extraction of essential oils by hydrodistillation of four aromatic species: Conditioning, extraction conditions, yield and chemical composition - Olascuaga-Castillo, Karyn Alicia (2024)
Essential oils are one of the most important products in the agricultural and food industry, as they are obtained from aromatic plants using various extraction techniques, such as steam distillation or hydrodistillation. However, these methods present challenges, such as low efficiency, limited selectivity, extensive use of solvents and long extraction times. Moreover, the quality of the oils obtained can be affected by hydrolysis or oxidation due to the duration and amount of water used in the process. This review updates the information on Clevenger-type hydrodistillation extraction of four high-value commercial plant species: Matricaria chamomilla, Rosmarinus officinalis, Origanum vulgare, and Eucalyptus spp. The aim is to evaluate the results of original articles, considering the origin and characteristics of the plant material, extraction conditions, yield and metabolites. The search covered a 10-year period (2013-2023) in Scopus, Web of Science, PubMed, and Google Scholar, using keywords such as species names and terms “essential oils” and “hydrodistillation”, with Boolean connectors such as OR, AND or NOT. The results show that quality and yield are influenced by factors such as geographical regions of origin, plant part used, drying techniques or extraction conditions (plant material/water ratio, extraction temperature, extraction time, etc.). In future research, the conditions associated with the plant material and the extraction process need to be optimized in obtaining high quality essential oils.